07.30: Ways of improving the stability design calculations of cold‐formed columns. (13th September 2017) - Belyy, Grigoriy; Kuznetsov, Aleksei
ABSTRACT: The article presents the theoretical basis of engineering approach to the stability resistance calculation of cold‐formed columns subjected to an axial or eccentric compression. The research is based on an analytical stability solution and Eurocode provisions in terms of determining the reduced cross‐section in a combined action loading. It is demonstrated, that the reduced cross‐section, defined by the limit state of the column without reduction, in most cases has sufficient accuracy for engineering practice. Taking this assumption into account the engineering algorithm is designed for stability calculations by: flexural mode relatively the major axis; flexural‐torsional mode relatively the minor axis and overall mode. The results of stability calculations are demonstrated on examples of pin‐pin end restrained cold‐formed columns with high degree of section reduction. Stability resistance coefficients depending on column slenderness and load eccentricities are given. The degree of reduction influence on the overall stability is highlighted. The comparison with Eurocode results and authors experimental studies is also given.